CHARACTER EDUCATION AND MORAL VALUE IN 2D ANIMATION FILM ENTITLED "PENDETA BANGAU" - Anggara, I Gede Adi Sudi; Santosa, Hendra; Udayana, A.A. Gde Bagus (Capture : Jurnal Seni Media Rekam, 2019)
Character is a very important and fundamental matter in a child's development. Character education has the same orientation with moral education, whereas moral education is very important in directing young generation to become good people through good values approach. In the midst of current IT advances, animated films are one of the effective and interesting media in transferring the values of character education and moral messages to children. The 2D animated film entitled Pendeta Bangau (The Priestess of Stork) is an animated film which source of story comes from Balinese folklore entitled Pedanda Baka. The aim of this study is to discuss the values of character education and moral messages/values contained in the animated film entitled â€œPendeta Bangauâ€. This study uses qualitative research methods with qualitative data analysis techniques model of Miles and Huberman. The result of this study shows that the character education values from the animated film entitled Pendeta Bangau contains the values of honesty, tolerate, friendship / communicative, love of peace, and curiosity. While the moral message/value was seen in the final/end of film, namely the Bangau (stork) died due to its immorality. Its Bangau dead is related to the principal of Prarabda Karmaphala, namely Bangau, gets the results of his behavior in the present, and is now available without being there anymore.